IMPLEMENTATION OF QUALITY MANAGEMENT OF RELIGIOUS VALUES EDUCATION FOR STUDENTS AT AN-NAHDLIYIN ELEMENTARY MADRASAH DUKUH TENGAH BUDURAN SIDOARJO - Intan Fauziah; Nurul Iman; Katni (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
This research was conducted with the aim of knowing the concept of management of religious values education, the implementation of the management concept of religious values education and the implementation of management of religious values education among students at Madrasah Ibtidaiyah An-Nahdliyin Dukuh Tengah Buduran Sidoarjo. . Researchers will dig deeper into the formation of religious values in educational institutions which are implemented in daily attitudes and behavior both in the school environment and in the Islamic Religious Education learning process. The type of research used is field research. The nature of the following research is descriptive qualitative, meaning that this research is descriptive research, generally carried out by interviews and observations. The results of this research are: 1) Education quality management carried out by Madrasah Ibtidaiyah Annahdliyin by implementing the POAC concept, namely implementation, organization, execution and supervision, has met the standards and targets set by Madrasah Ibtidaiyah Annahdliyin. 2) The results of the implementation of religious values education are in accordance with the standards used with the strengthening of religious knowledge and the implementation of religious life has gone according to the wishes and plans of Madrasah Ibtidaiyah Annahdliyin. It is also in accordance with the vision of Madrasah Ibtidaiyah Annahdliyin, namely the formation of people who excel in IMTAQ and Science and Technology and have good morals.